Effectiveness Of The Audit Function As An Internal Control Tool - Siti Alya Noviani; Sri Trisnaningsih (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the effectiveness of the audit function as an internal control tool. Audit as an internal control tool is very important for the efficiency and productivity of company operations. Internal audit is a process in which internal auditors review and assess the internal control systems and procedures used by an organization. Internal audits can assist in carrying out fixed asset acquisition procedures, improve management performance, and help companies maintain internal control. The internal audit function also makes it possible to measure and assess how effective other internal control components are, assisting management in implementing effective internal control. The results of this research are a very important tool for management to ensure that company operations run well and efficiently.